2013
DOI: 10.1186/1741-7015-11-160
|View full text |Cite
|
Sign up to set email alerts
|

Targeting insulin resistance in type 2 diabetes via immune modulation of cord blood-derived multipotent stem cells (CB-SCs) in stem cell educator therapy: phase I/II clinical trial

Abstract: BackgroundThe prevalence of type 2 diabetes (T2D) is increasing worldwide and creating a significant burden on health systems, highlighting the need for the development of innovative therapeutic approaches to overcome immune dysfunction, which is likely a key factor in the development of insulin resistance in T2D. It suggests that immune modulation may be a useful tool in treating the disease.MethodsIn an open-label, phase 1/phase 2 study, patients (N = 36) with long-standing T2D were divided into three groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(92 citation statements)
references
References 67 publications
(98 reference statements)
2
89
0
1
Order By: Relevance
“…Based on their unique properties in immune modulation , we developed a new technology, called Stem Cell Educator (SCE) therapy, by using CB‐SCs in a closed‐loop system that circulates a patient's blood through a blood cell separator, briefly co‐cultures the patient's lymphocytes with adherent CB‐SCs in vitro, and returns the “educated” lymphocytes (but not the CB‐SCs) to the patient's circulation . A single treatment with SCE therapy provides lasting reversal of autoimmunity, leading to the regeneration of islet β cells and improvement of metabolic control in individuals with longstanding T1D and T2D . Specifically, a recent phase I/II study demonstrated the safety and feasibility of SCE therapy in the treatment of alopecia areata (AA) , one of the most common T cell‐mediated autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Based on their unique properties in immune modulation , we developed a new technology, called Stem Cell Educator (SCE) therapy, by using CB‐SCs in a closed‐loop system that circulates a patient's blood through a blood cell separator, briefly co‐cultures the patient's lymphocytes with adherent CB‐SCs in vitro, and returns the “educated” lymphocytes (but not the CB‐SCs) to the patient's circulation . A single treatment with SCE therapy provides lasting reversal of autoimmunity, leading to the regeneration of islet β cells and improvement of metabolic control in individuals with longstanding T1D and T2D . Specifically, a recent phase I/II study demonstrated the safety and feasibility of SCE therapy in the treatment of alopecia areata (AA) , one of the most common T cell‐mediated autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%
“…As far as we know, this is the first study to evaluate fasting C-peptide-derived indices of pancreatic b-cell function and insulin sensitivity in relation to microvascular complications in T2DM. We used fasting plasma C-peptide instead of fasting insulin, because C-peptide is a by-product of insulin synthesis and is released at equal levels, while the accuracy of HOMA-B and HOMA-IR calculated using fasting insulin was limited, owing to the external insulin injections and other treatments in T2DM patients [7]. We simultaneously combined pancreatic b-cell function with insulin resistance to evaluate both factors' influence on microalbuminuria in T2DM, in contrast with previous studies which assessed the association of microalbuminuria with a single factor, e.g., pancreatic b-cell function or insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a phase I/II clinical trial showed that UCB-derived multipotent progenitors that coexpress CD45 can educate autologous peripheral blood mononuclear cells in a closed loop system and can attenuate immunological regulators in type 2 diabetes. Insulin sensitivity was improved after treatment with some recovery of islet b cell function, perhaps through balancing of Th1/Th2/Th3 cytokine production [93].…”
Section: Ucb Cells Secretome As An Essential Accessory In Regenerativmentioning
confidence: 99%